Exploring the Effectiveness of Bilingual Dictionaries in Academic Writing Development - Norpoʻlatova Nozima Yusufxon qizi (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article examines the role and effectiveness of bilingual dictionaries in supporting the academic writing development of English as a Foreign Language (EFL) learners. Academic writing requires precise vocabulary, correct grammar, and the ability to convey ideas clearly, which can be challenging for EFL students. Bilingual dictionaries offer a practical resource for understanding unfamiliar words, translating terms, and enriching lexical knowledge. The study investigates how intermediate and advanced learners utilize bilingual dictionaries during writing tasks, their influence on vocabulary acquisition, accuracy, and overall writing quality. Classroom observations, learner surveys, and prior research indicate that bilingual dictionaries facilitate independent learning, improve word choice, and increase confidence in writing, though overreliance may impede language development if not combined with other learning strategies. Pedagogical implications for teachers and curriculum designers are also discussed.